2016
DOI: 10.1016/j.neurobiolaging.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes may precede proteostatic dysfunction in a  Drosophila model of amyloid beta peptide toxicity

Abstract: Amyloid beta (Aβ) peptide aggregation is linked to the initiation of Alzheimer's disease; accordingly, aggregation-prone isoforms of Aβ, expressed in the brain, shorten the lifespan of Drosophila melanogaster. However, the lethal effects of Aβ are not apparent until after day 15. We used shibireTS flies that exhibit a temperature-sensitive paralysis phenotype as a reporter of proteostatic robustness. In this model, we found that increasing age but not Aβ expression lowered the flies' permissive temperature, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
(90 reference statements)
3
12
0
Order By: Relevance
“…Increased histidine levels were observed in response to acute stress and artificial selection for stress resistance in Drosophila ( Malmendal et al, 2013 ; Overgaard et al, 2007 ). Histidine has earlier been shown to increase in Drosophila expressing both benign and toxic Aβ ( Ott et al, 2016 ), which is very similar to the present system where histidine increased in Aβ42 flies, independent of co-expression of PI3K. In humans, high histidine was found in urine from patients with Parkinson's disease ( Luan et al, 2015 ), and additional high levels of lysine were found in plasma from patients with mild cognitive impairment ( Trushina et al, 2013 ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Increased histidine levels were observed in response to acute stress and artificial selection for stress resistance in Drosophila ( Malmendal et al, 2013 ; Overgaard et al, 2007 ). Histidine has earlier been shown to increase in Drosophila expressing both benign and toxic Aβ ( Ott et al, 2016 ), which is very similar to the present system where histidine increased in Aβ42 flies, independent of co-expression of PI3K. In humans, high histidine was found in urine from patients with Parkinson's disease ( Luan et al, 2015 ), and additional high levels of lysine were found in plasma from patients with mild cognitive impairment ( Trushina et al, 2013 ).…”
Section: Resultssupporting
confidence: 84%
“…The Aβ42-induced metabolite changes agree with those caused by toxic Arctic Aβ42 (E22G) relative to non-toxic levels of Aβ42 and Aβ40 in abdomens ( Ott et al, 2016 ) in that we see an increase in histidine and a decrease in maltose in both systems ( Fig. 4 B,C).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The accumulation of maltose in the chill-susceptible species could therefore function to reduce the likelihood of chill injury following cold exposure, but may also be a more general and non-specific response to stressful conditions. Increased levels of maltose have previously been linked to a wide range of different stressors like inbreeding, thermal stress, starvation and artificial expression of the amyloid β-peptide (Pedersen et al, 2008;Malmendal et al, 2013;Ott et al, 2016).…”
Section: Metabolite Response To Cold Exposurementioning
confidence: 99%